2010
DOI: 10.2987/09-5926.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of West Nile Virus Dose and Extrinsic Incubation Temperature on Temporal Progression of Vector Competence in Culex pipiens quinquefasciatus

Abstract: Culex pipiens quinquefasciatus were fed blood containing either 7.0 ± 0.1 logs plaque-forming units (pfu)/ml (high dose) or 5.9 ± 0.1 logs pfu/ml (low dose) of West Nile virus and held at extrinsic incubation temperatures (EIT) of 28°C or 25°C. Approximately 20 mosquitoes per dose were collected after incubation periods (IP) of 4, 6, 8, and 12 days postinfection (dpi). Infection rates were influenced by EIT and virus dose but not by IP. Body titer was significantly higher for mosquitoes fed the high dose and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 17 publications
0
65
0
Order By: Relevance
“…Studies in Florida showed much higher infection and dissemination rates at one-week post-exposure at comparable or lower doses, even at lower temperatures (transmission rates were not mentioned). 30 Similarly, although studies in California (which did cite transmission rates) showed variability in results on the basis of comparable viral titers, mosquitoes there tended to have higher vector competency than those of Galápagos. 32,34 In our own study, transmission ability in the first two weeks of infection was less than 10%, which suggests a lower WNV risk for Galápagos fauna if other more-competent mosquito vectors are not present.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in Florida showed much higher infection and dissemination rates at one-week post-exposure at comparable or lower doses, even at lower temperatures (transmission rates were not mentioned). 30 Similarly, although studies in California (which did cite transmission rates) showed variability in results on the basis of comparable viral titers, mosquitoes there tended to have higher vector competency than those of Galápagos. 32,34 In our own study, transmission ability in the first two weeks of infection was less than 10%, which suggests a lower WNV risk for Galápagos fauna if other more-competent mosquito vectors are not present.…”
Section: Discussionmentioning
confidence: 99%
“…32,[36][37][38] Generally, longer incubation periods, higher viral doses, and higher temperatures are expected to yield higher rates of infection. 30,32,39 However, Cx. quinquefasciatus in Australia was shown to be a highly competent vectors when exposed to a dose of only 10 4.0±0.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations